Abductive Analysis, theorizing qualitative research - Garcés Vélastegui, Pablo (Comentario Internacional: Revista del Centro Andino de Estudios Internacionales, 2017)
Reseña del libro de Iddo Tavoty y Stefan Timmermans, Abductive Analysis, theorizing qualitative research, Chicago: University of Chicago Press, 2014.